Konflik Batin Tokoh Utama dalam Antologi Cerpen Kekalahan Karya Ruddin: Kajian Psikologi Sastra - Pujiarti, Hayat; Tiyana, Maya Syva; Samudra, Achmad Deli (Literature Research Journal, 2024)
Penelitian ini berusaha mendeskripsikan konflik batin yang terdapat pada Tokoh Utama dalam Antologi Cerpen Kekalahan Karya Ruddin: Kajian Psikologi Sastra. Tujuan penelitian ini untuk mengetahui konflik batin tokoh utama dalam antologi cerpen kekalahan karya Ruddin: kajian Psikologi sastra. Penelitian dilakukan dengan menggunakan metode deskriptif kualitatif. Data dalam penelitian ini berupa bentuk kata, kalimat, dan penggalan paragraf yang mendeskripsikan bentuk konflik batin tokoh utama dalam antologi cerpen kekalahan karya Ruddin. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah teknik studi pustaka, yaitu teknik baca dan catat. Hasil dari penelitian ini berupa lima aspek teori Abraham Maslow pertama, kebutuhan fisiologis yang terdapat kurangnya kebutuhan dasar, kedua kebutuhan akan rasa aman yang mencakup ketakutan, kecemasan, dan tekanan emosional, ketiga kebutuhan sosial yang terdapat kurangnya kasih sayang, keempat kebutuhan harga diri yang mencakup perwujudan, penerimaan diri, kelima kebutuhan aktualisasi diri yang mencakup perasaan kecewa, khawatir, malas, kesal, heran, panik, dan menyesal.The Inner Conflict of the Main Character in Ruddin's Anthology of Short Stories of Defeat: A Study of Literary PsychologyThis research attempts to describe the inner conflict found in the main character in the short story anthology "Defeat" by Ruddin: Literary Psychology Study. The aim of this research is to determine the inner conflict of the main character in the short story anthology "defeat" by Ruddin: a literary psychology study. The research was conducted using qualitative descriptive methods. The data in this research are in the form of words, sentences and paragraph fragments that describe the form of inner conflict of the main character in the short story anthology "defeat" by Ruddin. The data collection technique used in this research is the library study technique, namely the reading and note-taking technique. The results of this research are five aspects of Abraham Maslow's theory, firstly, physiological needs which contain a lack of basic needs, secondly the need for security which includes fear, anxiety and emotional stress, thirdly social needs which contain a lack of affection, fourthly the need for self-esteem which includes includes realization, self-acceptance, the five needs for self-actualization which include feelings of disappointment, worry, laziness, annoyance, surprise, panic and regret.